Development of microalgal biofilm for wastewater remediation: from mechanism to practical application. Issue 11 (22nd July 2021) - Hu, Yingbing; Xiao, Yu; Liao, Kang; Leng, Yunyue; Lu, Qian
Abstract: The high cost of biomass harvesting by centrifugation and high safety risks of collected algal biomass by chemical flocculation are serious problems jeopardizing the industrial implementation of microalgae bio‐products. Recently, microalgae immobilization is regarded as a promising technology with the potential of lowering biomass production cost and ensuring biomass safety in the industry. Therefore, microalgal biofilms, an effective and affordable way to immobilize algal cells, are emerging into the limelight. This paper summarizes the progress achieved in biofilm system design and biofilm formation mechanisms. Newly designed algal biofilm systems are compared to demonstrate their advantages and weaknesses. Besides, mechanisms associated with the two steps –initial attachment of microalgae and biofilm thickening – of biofilm formation are discussed in this paper. Factors such as substratum material, algal strain and operational parameters, which could impact the formation and operation of algal biofilm, are demonstrated. Efforts devoted to the industrial application of algal biofilm to treat wastewater are discussed. The biotechnology of microalgal biofilm is currently at the critical stage of developing from fundamental research to industrial implementation. Undeniably, there are still many problems that limit the wide use of algal biofilm for biomass production and wastewater treatment. In this paper, we present some potential solutions to current problems and discuss the development trends of algal biofilm in the foreseeable future. It is expected that by addressing current problems microalgal biofilm will be widely used at the industrial scale. © 2021 Society of Chemical Industry (SCI).